2018
DOI: 10.1080/09537325.2018.1459539
|View full text |Cite
|
Sign up to set email alerts
|

University spin-off firms’ struggle with openness in early knowledge relationships: in search of antecedents and outcomes

Abstract: Little is known about how young high-tech ventures create openness in their knowledge networks. This paper explores the influence of antecedent resources on openness in knowledge networks, seen as diversity in knowledge partners, and explores the impact of openness on growth. The results from 105 university spin-off firms suggest that three antecedents positively influence openness, namely, founders' prestart experience, education and innovation experience, and one negatively, namely, size of the founding team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…A management team with a wide range of managerial skills and experience can increase OI capabilities (Wynarczyk, 2013). The founders' prior experience, education and innovation capabilities determine how open the SME will be to external knowledge networks (Taheri et al, 2018). Personal characteristics like openness and leadership are advantages (Lahi and Elenurm, 2015).…”
Section: Individual Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A management team with a wide range of managerial skills and experience can increase OI capabilities (Wynarczyk, 2013). The founders' prior experience, education and innovation capabilities determine how open the SME will be to external knowledge networks (Taheri et al, 2018). Personal characteristics like openness and leadership are advantages (Lahi and Elenurm, 2015).…”
Section: Individual Determinantsmentioning
confidence: 99%
“…Some studies have shown possible advantages for SMEs, in particular, an improved capability to cope with the limitations of being a small business that lacks resources and skills (Bianchi et al, 2010;Van De Vrande et al, 2009;Chesbrough et al, 2006). Other studies have shown possible disadvantages: SMEs are highly sensitive not only to the costs of OI but also to its risks, and such risks may hinder their development (Ham et al, 2017;Huang et al, 2015;Taheri et al, 2018). Use of OI seems to be favoured by some SME characteristics, in particular, flexibility, informality and risk-taking and hindered by others, particularly small size, lack of human and financial resources, limitations of scale and absence of technological assets (Spithoven et al, 2013;Ahn et al, 2015;Basco and Calabro, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The research framework. (Heirman and Clarysse, 2004;Kitagawa and Robertson, 2012;Mozhdeh Taheri and Van Geenhuizen, 2018;Mustar et al, 2006;Visintin and Pittino, 2015). A spin-off starts firstly from the knowledge developed and accumulated in PO by individuals who recognized the chance to exploit it in a business, taking advantage of relational factors (Del Giudice et al, 2013).…”
Section: Theoretical Background and Research Frameworkmentioning
confidence: 99%
“…Further, Hypothesis 2, on positive association of size of founding teams, is not supported for early and later patterns of internationalization. This may be understood as caused by existing of an optimum size for teams, not captured in our analysis, above which team members become less productive, for example, in creating consensus about important decisions (Onkelinx et al, 2016;Taheri et al, 2018). The generic nature of founding team size, not referring to specific capability in building international networks, could add to the lack of association.…”
Section: Hypotheses Testingmentioning
confidence: 95%
“…With regard to domestic networks, young firms develop supporting capabilities through interaction in social network relations in the home country Vahlne, 2003, 2009;Milanov and Fernhaber, 2014). The idea is that the larger the domestic network, the more powerful capabilities tend to be in connecting domestically with firms abroad, but with larger size, management challenges may emerge (Taheri et al, 2018). In particular, networks outside academic circles, including e.g.…”
Section: Accordingly We Phrasementioning
confidence: 99%